A kind of anti-rust heat-insulating coating and its preparation method and application
By modifying anti-rust and heat-insulating coatings of silicate and hollow glass microbead materials, the shortcomings of existing coatings in terms of weather resistance, thermal insulation and environmental impact are solved, and the effects of high adhesion, corrosion resistance and thermal insulation are achieved.
Patent Information
- Application Number
- CN202310976953.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-08-03
AI Technical Summary
The existing color steel plate coatings have shortcomings in weather resistance, durability and heat insulation effects, and waste gas and waste will be generated during construction, which will greatly pollute the environment.
Anti-rust insulation coatings with modified silicate and hollow glass microbead materials are used to increase the formation of hydroxyl functional groups and iron silicate by modifying silicates, thereby improving the adhesion and corrosion resistance of the coating; alkali etching modification of hollow glass microbeads enhances the durability and thermal insulation effect of the coating.
It achieves good adhesion, corrosion and rust resistance and heat insulation of the coating, reduces energy consumption and environmental pollution, and simplifies the construction process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an anti-rust and heat-insulating coating and a preparation method and application thereof. Background Art
[0002] The factory building is generally made of color steel plates and color steel tiles. The weather in the south changes quickly, and the temperature is high in summer. The outer surface of the factory building is often exposed to the sun, and there may be heavy rain after the exposure, so the coating on the outer surface of the factory building is greatly damaged. In addition, it will accelerate the rust of the color steel plate. This is why many factory roofs in the south of China that have been used for a long time are iron yellow patches. With the development of society and the progress of science and technology, the market has put forward higher and higher requirements for the weather resistance, durability, functionality, etc. of coatings. The coatings for color steel plates in the existing technology mostly use organic components, but organic components have poor weather resistance, yellowing of the coating, and problems such as shedding, cracking and fading of the coating layer after long-term use, which cannot meet the higher requirements in terms of durability. The use of oily coatings will generate waste gas and waste during production and construction, which will cause great pollution to the environment. For factory buildings in the south, the temperature in the factory building is also very high in summer, which requires a lot of electricity to maintain a suitable temperature. If a layer of thermal insulation coating can be applied on the surface, it can greatly reduce energy consumption and reduce factory electricity expenditure.
[0003] Traditional thermal insulation color steel plate coatings mainly use water-based epoxy resin as a film-forming substance, which has poor weather resistance, and re-coating cannot solve the problem of iron yellow rust spots. The functional fillers used have poor thermal insulation and reflection effects and cannot achieve a full and bright coating. The prior art discloses a long-term application period quick-drying water-based heat reflective thermal insulation coating and a preparation method thereof. The raw materials used in the method contain volatile organic compounds such as anhydrous diluents and drying agents, which will evaporate rapidly during construction, resulting in a high VOC concentration during construction, which is more harmful to the human body. Moreover, its components are AB components, which are more troublesome to construct and have the phenomenon of incomplete curing.
[0004] Therefore, it is urgent to develop an anti-rust coating for color steel plates which is simple to construct, environmentally friendly in materials, can solve the problem of secondary recoating, and has an anti-aging coating which has a good house insulation effect. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides an anti-rust and heat-insulating coating having good coating adhesion and anti-corrosion and anti-rust properties, as well as good durability, salt spray resistance and heat-insulating effect.
[0006] The invention also provides a method for preparing the rust-proof and heat-insulating coating.
[0007] The invention also provides application of the rust-proof and heat-insulating coating.
[0008] The first aspect of the present invention provides an anti-rust and heat-insulating coating, wherein the raw materials for preparing the anti-rust and heat-insulating coating include the following components in parts by weight:
[0009] 0.3-0.6 parts of cellulose ether;
[0010] Dispersant 0.3-0.7 parts;
[0011] Wetting agent 0.3-0.5 parts;
[0012] Defoaming agent 0.3-0.5 parts;
[0013] Stabilizer 0.5-1 part;
[0014] 0.2-0.5 parts of anti-settling agent;
[0015] 10-30 parts of heavy calcium;
[0016] 10-20 parts of titanium dioxide;
[0017] 3-10 parts of mica powder;
[0018] Anti-flash rust agent 0.5-1 part;
[0019] 5-10 parts of acrylic emulsion;
[0020] 25-45 parts of modified silicate and hollow glass microsphere materials;
[0021] Thickener 0.3-1 part;
[0022] 18 to 25 parts of water.
[0023] According to the first aspect of the present invention, there are at least the following beneficial effects:
[0024] (1) The present invention modifies silicate, increases the modulus of silicate and adjusts the pH value to obtain more hydroxyl functional groups. It has a strong condensation ability for trivalent iron ions that corrode steel. At the same time, silicate with an appropriate modulus reacts with the hydroxyl groups on the surface of the steel to form a strong protective film with iron silicate as the main body. This dense passivation film has a good adhesion effect. After modification, the pH of the system is high enough to reach greater than 12, which can inhibit the oxidation reaction of iron. At the same time, the generated iron silicate passivation layer can isolate air and prevent the occurrence of flash rust. After testing, the coating adhesion test after material modification is 5B grade, and the anti-corrosion and anti-rust performance measured according to the salt spray test specification ASTM B117-03 is 960h without blistering, corrosion width is less than 2mm, and there is no rust spot.
[0025] (2) The present invention performs alkaline etching on the hollow glass microspheres, and corrodes grooves on the surface of the hollow glass microspheres, making it easier for the polymer chain segments of the resin matrix to enter the grooves on the surface of the microspheres, producing an "anchoring" effect, and increasing the interaction force between the two interfaces; on the other hand, after etching, a large number of silicon hydroxyl groups are generated on the surface of the microspheres, which is beneficial to increase the interfacial bonding force between the two phases. Therefore, through the modification of hollow glass microspheres, the adhesion of the coating can be enhanced, and the durability and temperature resistance of the coating can be better. In addition, due to the reflection of sunlight by titanium dioxide and hollow glass microspheres, more than 85% of the sun's heat can be blocked on the surface of the substrate coated with reflective heat insulation coating, thereby reducing the energy consumption of air conditioning and improving the working environment of the staff. After testing, the temperature difference between the outer coating and the reverse insulation of the roof color steel plate is about 10.3°C, and the temperature difference between the outdoor temperature and the indoor temperature can reach about 5.2°C.
[0026] (3) The present invention mainly uses inorganic materials, which are environmentally friendly, have low VOC emissions, and cause little air pollution. Appropriate addition of organic emulsion as elastic modification material can make up for the shortcomings of silicate in the curing process, such as large volume shrinkage and easy cracking of the coating film. The finished product can be constructed by spraying or rolling, which is very simple and does not require mixing and stirring again. Especially for the secondary reinstallation of the factory building, it can be painted with rust without rust removal, and direct construction will not rust again.
[0027] According to some embodiments of the present invention, the raw materials for preparing the anti-rust and heat-insulating coating include the following components in parts by weight:
[0028] 0.5 parts of cellulose ether;
[0029] 0.5 parts of dispersant;
[0030] Wetting agent 0.3 parts;
[0031] 0.3 parts of defoaming agent;
[0032] 0.4 parts of stabilizer;
[0033] 0.3 parts of anti-settling agent;
[0034] 10 parts of heavy calcium;
[0035] 15 parts of titanium dioxide;
[0036] 7 parts of mica powder;
[0037] 0.7 parts of anti-flash rust agent;
[0038] Acrylic emulsion 9 parts;
[0039] 35.5 parts of modified silicate and hollow glass microsphere materials;
[0040] Thickener 0.5 parts;
[0041] 20 parts water.
[0042] According to some embodiments of the present invention, the cellulose ether is at least one of methyl cellulose ether, hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.
[0043] According to some embodiments of the present invention, the cellulose ether is hydroxyethyl cellulose ether, and the viscosity is 30,000 viscosity; (250hbr; American Aqualon).
[0044] The function of cellulose ether is to retain water and thicken.
[0045] According to some embodiments of the present invention, the dispersant is at least one of an ammonium salt and an onium salt.
[0046] Preferably, the ammonium salt comprises a quaternary ammonium salt, and San Nopco SN-5027 polycarboxylate amine salt dispersant is used.
[0047] According to some embodiments of the present invention, the wetting agent is at least one of polyether-modified polysiloxane and organic fluorine polymer. In this embodiment, Haichuan PE-100 wetting agent is used.
[0048] According to some embodiments of the present invention, the defoaming agent is at least one of organosiloxane, polyether, imine and amide.
[0049] According to some embodiments of the present invention, the stabilizer is at least one of quaternary ammonium salts, tertiary amines and organic and inorganic silicides.
[0050] Among them, stabilizers are mainly used to improve the storage time, viscosity stability and construction performance of the coating.
[0051] According to some embodiments of the present invention, the anti-settling agent is sodium bentonite (BP-188 bentonite from Zhejiang Huate New Materials Co., Ltd.).
[0052] It mainly prevents water separation and flocculation, allowing the paint to maintain a uniform can opening effect for a long time.
[0053] According to some embodiments of the present invention, the heavy calcium is calcite powder with a whiteness of ≥90 and a fineness of 600-800 mesh. Preferably, the heavy calcium is calcite powder with a whiteness of ≥90 and a fineness of 800 mesh (Guangyuan Chemical GY-316 calcite powder).
[0054] It mainly plays the role of filling and covering.
[0055] According to some embodiments of the present invention, the titanium dioxide is rutile (Shandong Dongjia SR-2377 titanium dioxide).
[0056] Rutile titanium dioxide has stronger weather resistance and aging resistance, stronger ozone and UV resistance, and high reflectivity for visible light with a wavelength of 400 to 700 nm.
[0057] According to some embodiments of the present invention, the whiteness of the mica powder is ≥75.
[0058] According to some embodiments of the present invention, the fineness of the mica powder is 600-800 mesh.
[0059] Preferably, the fineness of the mica powder is 800 mesh (Chuzhou Pagoda WJ-6 mica powder).
[0060] According to some embodiments of the present invention, the flash rust inhibitor is an organic corrosion inhibitor comprising an organic acid amine (R-755 flash rust inhibitor from Kunshan Qi Chuang Chemical Co., Ltd.).
[0061] It can effectively inhibit the flash rust phenomenon that occurs during the drying process of water-based paint on substrates such as carbon steel, tinplate, galvanized sheet, cold-rolled sheet, etc., and can solve the problem of rust on water-based paint film in a short period of time after it dries.
[0062] According to some embodiments of the present invention, the acrylic emulsion is at least one of a pure acrylic emulsion and a silicone acrylic emulsion.
[0063] According to some embodiments of the present invention, the acrylic emulsion is at least one of Rosef Emulsion 5588 and Heye Chemical J504.
[0064] According to some embodiments of the present invention, the thickener is at least one of a hydrophobically modified alkali-swellable thickener, a nonionic polyurethane-based thickener, and an alkali-swellable acrylic-based thickener.
[0065] According to some embodiments of the present invention, the thickener may be SR-800 produced by Foshan Heye Chemical Co., Ltd.
[0066] According to some embodiments of the present invention, the modified silicate and hollow glass microsphere material is synthesized through two steps of modification of the silicate and modification of the hollow glass microsphere.
[0067] According to some embodiments of the present invention, the modified preparation method of silicate comprises the following steps:
[0068] Mixing silicate, silica sol, organosilicon coupling agent and stabilizer, heating and stirring to obtain modified silicate solution;
[0069] According to some embodiments of the invention, the silicate comprises at least one of potassium silicate and sodium silicate.
[0070] Preferably, the silicate is potassium silicate.
[0071] Among them, potassium silicate is a colorless or slightly yellow translucent to transparent glassy substance, which is hygroscopic and has a strong alkaline reaction. Silica sol is a colloidal solution, odorless and non-toxic. Silica sol is a dispersion of nano-scale silicon dioxide particles in water or solvent. SiO2 in silica sol contains a large amount of water and hydroxyl groups, so silica sol can also be expressed as SiO2·nH2O. Due to the addition of silica sol, the hydroxyl groups will be reduced through heating reaction, which will change the pH value of the system. The two particle size distribution peaks of silica sol will change, and the active silicon in potassium silicate will be deposited on the rearranged particles of silica sol, forming a new particle size distribution that is different from the original silica sol and potassium silicate.
[0072] According to some embodiments of the present invention, the organosilicon coupling agent is γ-glycidyloxypropyltrimethoxysilane (CAS No.: 2530-83-8; Chengdu McCarthy Chemical Co., Ltd.).
[0073] According to some embodiments of the present invention, the temperature of the heat treatment is 50-75°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, or 75°C.
[0074] According to some embodiments of the present invention, the stirring time is 30 to 60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, or 60 min.
[0075] According to some embodiments of the present invention, the modified preparation method of the silicate comprises the following specific steps:
[0076] Put silicate and silica sol in a magnetic stirrer, turn on the magnetic stirring, adjust the temperature to 50°C, add the organosilicon coupling agent dropwise after the temperature stabilizes, then add the quaternary ammonium salt stabilizer, continue stirring for 30 minutes after the addition, then increase the temperature to 75°C, stir and react for 30 minutes to obtain a modified silicate solution.
[0077] After a special modification, silicate can obtain more hydroxyl functional groups and fine particles, which have strong penetration into the base layer and can penetrate into the base layer through capillaries. It has a strong condensation ability for trivalent iron ions that corrode steel. At the same time, silicate with a suitable modulus reacts with the hydroxyl groups on the surface of steel to form a solid protective film with iron silicate as the main body. This dense passivation film is insoluble in water, has high hardness and strong adhesion, and can react with many metal ions to form complexes with good adhesion. 4Fe+3O2+XH2O==2Fe2O3·XH2O, 2Fe2O3·XH2O is the component of rust, which can also be written as Fe x [(OH)3] n, and the pH of the system is high enough, reaching greater than 12, which can inhibit the occurrence of this reaction. At the same time, the iron silicate passivation layer produced can also prevent the occurrence of flash rust. Wherein, the quaternary ammonium salt stabilizer can be used as the quaternary ammonium salt stabilizer in the raw material of the anti-rust and heat-insulating coating preparation.
[0078] According to some embodiments of the present invention, the modulus of the silicate is 2.8 to 3.8, for example, 2.8, 3, 3.2, 3.4, 3.6, or 3.8.
[0079] According to some embodiments of the present invention, the modulus of the modified silicate solution is 4 to 4.2, for example, 4, 4.1, or 4.2.
[0080] According to some embodiments of the present invention, the pH of the modified silicate solution is greater than 12.
[0081] According to some embodiments of the present invention, the solid content of the modified silicate solution is 27-29%; the organic content is <2%.
[0082] According to some embodiments of the present invention, the modification preparation method of the hollow glass microspheres comprises the following steps:
[0083] The hollow glass microspheres are pretreated and heat treated, and then the modified silicate is added to react to obtain the modified silicate and hollow glass microsphere material.
[0084] Among them, hollow glass microspheres are specially processed glass microspheres, which are characterized by lower density and worse thermal conductivity than glass microspheres. Its main component is borosilicate, which has the characteristics of high compressive strength, high melting point, high resistivity, small thermal conductivity and thermal shrinkage coefficient.
[0085] According to some embodiments of the present invention, the pretreatment comprises adding hollow glass microspheres to a solvent, heating under reflux and stirring, and then performing reduced pressure filtration.
[0086] According to some embodiments of the present invention, the pressure of the reduced pressure filtration is 0.08-0.09 MPa.
[0087] According to some embodiments of the present invention, the time of the reduced pressure filtration is 3 to 5 minutes.
[0088] According to some embodiments of the present invention, the heating temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, or 80°C.
[0089] According to some embodiments of the present invention, the reflux stirring time is 30 to 40 min, for example, it can be 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, or 40 min.
[0090] According to some embodiments of the present invention, the heat treatment device is a resistance furnace.
[0091] According to some embodiments of the present invention, the temperature of the heat treatment is 200-250°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, or 250°C.
[0092] According to some embodiments of the present invention, the heat treatment time is 2 to 3 hours.
[0093] The purpose of heat treatment is to fully roast the organic impurities and moisture on the surface and in the cavity of the hollow glass microspheres to activate them.
[0094] According to some embodiments of the present invention, the mass ratio of the hollow glass microspheres to the modified silicate is 1:(2-3).
[0095] According to some embodiments of the present invention, the specific steps of reacting the hollow glass microspheres with the modified silicate are:
[0096] The hollow glass microspheres after heat treatment are added with modified silicate, heated and magnetic stirring is turned on, and then the modified silicate is added, and then the solution and precipitate are dispersed by ultrasonic oscillation, the precipitate is allowed to stand, and the impurities in the lower precipitate are filtered out, and the upper hollow glass microspheres and silicate solution are retained to obtain the modified silicate and hollow glass microsphere material.
[0097] According to some embodiments of the present invention, the heating temperature is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, or 60°C.
[0098] According to some embodiments of the present invention, the magnetic stirring time is 4 to 5 hours.
[0099] According to some embodiments of the present invention, the ultrasonic oscillation dispersion time is 40 to 50 minutes.
[0100] The second aspect of the present invention provides a method for preparing the above-mentioned anti-rust and heat-insulating coating, the preparation method comprising the following steps:
[0101] S1, weighing the modified silicate, hollow glass microsphere material and acrylic emulsion for pre-reaction;
[0102] S2, mixing cellulose ether, anti-settling agent, dispersant, wetting agent, defoaming agent, stabilizer, heavy calcium, titanium dioxide, mica powder and anti-flash rust agent;
[0103] S3, mixing the products obtained in step S1 and step S2, adding a thickener, stirring and reacting to obtain the anti-rust and heat-insulating coating.
[0104] According to some embodiments of the present invention, in step S1, the pre-reaction step is to place the modified silicate, the hollow glass microsphere material and the acrylic emulsion in a temperature-controlled reactor for stirring reaction.
[0105] Through the pre-reaction in the temperature-controlled reactor, the resin matrix and the hollow glass microspheres can react and overlap to form a long chain.
[0106] According to some embodiments of the present invention, in step S1, the temperature in the temperature-controlled reactor is 40-50°C.
[0107] According to some embodiments of the present invention, in step S1, the stirring speed is 500-550 r / min.
[0108] According to some embodiments of the present invention, in step S1, the stirring time is 30 to 40 minutes.
[0109] According to some embodiments of the present invention, in step S2, the stirring speed is 500-1000 r / min.
[0110] According to some embodiments of the present invention, in step S2, the stirring time is 5 to 25 minutes.
[0111] According to some embodiments of the present invention, in step S3, the stirring speed is 300-400 r / min.
[0112] According to some embodiments of the present invention, in step S3, the stirring time is 8 to 12 minutes.
[0113] The third aspect of the present invention provides the application of the above-mentioned anti-rust and heat-insulating coating in the field of metal material protection.
[0114] According to some embodiments of the present invention, the application includes coating on a color steel plate factory building.
[0115] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0116] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0117] Figure 1 This is a schematic diagram of the construction of the anti-rust and heat-insulating coating in Example 2 of the present invention;
[0118] Figure 2 A comparison diagram of rust spots of the anti-rust and heat-insulating coatings in Example 2 of the present invention and Comparative Example 2;
[0119] (a) shows the rust condition of the steel plate after 960 hours of application of the anti-rust and heat-insulating coating in Example 2; (b) shows the rust condition of the steel plate after 960 hours of application of the anti-rust and heat-insulating coating in Comparative Example 2. DETAILED DESCRIPTION
[0120] The embodiments of the present invention are described in detail below, and the same or similar reference numerals throughout the embodiments represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0121] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0122] In the description of the present invention, it should be understood that descriptions involving orientation, such as orientation or positional relationship indicated as up, down, etc., are based on the orientation or positional relationship shown in the embodiments, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0123] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0124] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0125] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0126] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0127] The reagents and equipment used in the present invention include:
[0128] Temperature control reactor: DFG-100, Yixing Feiyang Machinery Equipment Co., Ltd.
[0129] Resistance furnace: Test box resistance furnace SX-2.5-10D, Tianjin Test Instrument Co., Ltd.
[0130] Example 1
[0131] This embodiment provides a modified silicate and hollow glass microsphere material, and the specific preparation method steps are as follows:
[0132] (1) Modification of silicate: 100 g of potassium silicate with a modulus of 3.8 and 30 g of silica sol were placed in a magnetic stirrer, and the magnetic stirring was turned on. The temperature was adjusted to 50° C. After the temperature stabilized, 1.5 g of γ-glycidyloxypropyltrimethoxysilane was added dropwise, and then 1 g of quaternary ammonium salt stabilizer was added. After the addition, stirring was continued for 30 minutes, and the temperature was raised to 75° C. and stirred for reaction for 30 minutes. The solution was set aside as solution A. The obtained solution A had a modulus of 4.2, a solid content of 28±1%, a pH>12, and an organic content of <2%.
[0133] (2) Take 100 g of hollow glass microspheres with a particle size of 40 μm, add 200 g of isopropanol and 50 g of butyl ether, heat to 80° C., and reflux with stirring for 40 minutes. After the reaction is completed, vacuum filtration is performed to obtain the pretreated hollow glass microspheres.
[0134] (3) The pretreated hollow glass microspheres were placed in a resistance furnace and heat treated at 200°C for 2 h to fully roast the organic impurities and moisture on the surface and in the cavity of the hollow glass microspheres to activate them.
[0135] (4) Add 100 g of solution A to (3), adjust the temperature to 50°C and start magnetic stirring, add 150 g of solution A dropwise, let it react for 4 hours, and then disperse the solution and precipitate under ultrasonic oscillation for 40 minutes. The surface of the hollow glass microspheres fully reacts with the silicate solution to form an alkaline etching layer.
[0136] (5) The solution in (4) is allowed to settle and stand, and the impurities in the lower precipitate are filtered out, leaving the upper hollow glass microspheres and silicate solution, thereby obtaining a modified silicate and hollow glass microsphere material.
[0137] Example 2
[0138] This embodiment provides an anti-rust and heat-insulating coating, and the preparation method thereof specifically comprises the following steps:
[0139] (1) Weighing modified silicate, hollow glass microspheres and acrylic emulsion according to weight ratio, placing them in a temperature-controlled reactor, setting the temperature to 5° C., stirring at a speed of 500 r / min, and stirring for 30 min, to obtain a cross-linked product of hollow glass microspheres and acrylic emulsion①.
[0140] (2) Weigh water according to the weight ratio, start the high-speed disperser and adjust the stirring speed to 500 r / min, add cellulose ether and anti-settling agent into the water and stir for 5 minutes, then weigh the dispersant, wetting agent, defoaming agent and stabilizer according to the weight ratio and add them into the disperser, adjust the stirring speed to 1000 r / min, add heavy calcium, titanium dioxide, mica powder and anti-rust agent according to the weight ratio and stir at high speed for 20 minutes.
[0141] (3) Adjust the speed of the disperser to 300 r / min, add the cross-linked product ①, and then add the thickener and stir for 8 minutes to obtain the anti-rust and heat-insulating coating.
[0142] The modified silicate and hollow glass microspheres prepared in Example 1 were used to prepare an anti-rust and heat-insulating coating. The raw materials were prepared according to the weight percentages in Table 1. The effect of the anti-rust and heat-insulating coating obtained in this example on the steel plate was as follows: Figure 2 As shown in (a), there is no rust after 960 hours.
[0143] Comparative Example 1
[0144] This comparative example provides an anti-rust and heat-insulating coating, which differs from Example 2 in that only modified silicate material is added.
[0145] Comparative Example 2
[0146] This comparative example provides an anti-rust and heat-insulating coating, which is different from Example 2 in that unmodified silicate and hollow glass microsphere materials are added, wherein the effect of the prepared anti-rust and heat-insulating coating applied on the steel plate is as follows: Figure 2 (b) The red circle in the figure indicates the presence of rust spots.
[0147] Comparative Example 3
[0148] This comparative example provides an anti-rust and heat-insulating coating, which differs from Example 2 in that the amount of acrylic emulsion used is reduced.
[0149] Comparative Example 4
[0150] This comparative example provides an anti-rust and heat-insulating coating, which is different from Example 2 in that the preparation method does not include step (1), that is, no pre-mixing step is performed.
[0151] Table 1 Components and weight percentages of raw materials for preparation of Example 2 and Comparative Examples 1 to 4
[0152]
[0153]
[0154] Test Case
[0155] The performance of the anti-rust and heat-insulating coatings prepared in Example 2 and Comparative Examples 1 to 4 was tested respectively.
[0156] The performance test methods and standards used in this test case are as follows:
[0157] Salt spray test: ASTM B117-03;
[0158] Aging resistance: GB / 18950-2003;
[0159] Coating appearance and drying time: "JC / T 1040-2007";
[0160] Pencil hardness: GB / T 6739-1996;
[0161] Adhesion: GB / T9286-1998.
[0162] Brand 1 on the market: a reflective heat-insulating coating of a certain Duobang brand purchased online;
[0163] Brand 2 on the market: a paint for bridge steel structure purchased from a certain brand online;
[0164] Table 2 Performance test results of the anti-rust and heat-insulating coatings prepared in Example 2 and Comparative Examples 1 to 4
[0165]
[0166]
[0167] According to the results in Table 2, compared with Example 2, in Comparative Example 1, only modified silicate is added, and the thermal insulation effect of the coating is poor, and there is basically no thermal insulation effect. In Comparative Example 2, unmodified silicate and hollow glass microspheres are added, and the salt spray resistance of the coating will form a wider corrosion and rust spots, the hardness is also low, and the thermal insulation effect is not good. This is because the coating does not form a continuous and tight solidified layer, and the reflection effect of light is also weakened. In Comparative Example 3, the reduction in the amount of emulsion added will weaken the salt spray resistance and aging resistance of the coating, and the adhesion of the coating will also decrease a lot. This is because the inorganic material shrinks greatly in volume during the curing process, which will cause fine cracks, and adding an appropriate amount of emulsion can play a bonding and filling role for the cracks. In the preparation process, Comparative Example 4 was not pre-mixed, which would cause a certain decline in various properties. It can be seen that pre-mixing can make the resin matrix and the hollow glass microspheres react and overlap to form a long chain body first, thereby strengthening the coating structure.
[0168] Market brand 1 is a reflective heat-insulating coating of a certain Duobang brand purchased online. Its main materials are emulsion and hollow glass microspheres. The coating performance is mainly reflected in heat insulation, and its salt spray resistance and aging resistance are relatively poor. Market brand 2 is a coating for bridge steel structure of a certain Fangqi brand purchased online. Its main materials are epoxy resin and zinc powder. The coating performance is mainly reflected in salt spray resistance and aging resistance, but the performance in all aspects is not very good, and the heat insulation performance is basically non-existent.
[0169] In summary, the adhesion test of the anti-rust and heat-insulating coating of the present invention is 5B grade, the anti-corrosion and anti-rust performance is 960h without blistering, the corrosion width is less than 2mm, and there is no rust spot. Figure 2 As shown, the aging resistance is 500h without blistering, cracking and obvious powder loss; the temperature difference between the coating and the reverse insulation on the color steel plate is about 10.3℃, and the temperature difference between the outdoor temperature and the indoor temperature can reach about 5.2℃. The schematic diagram of the coating method is as follows Figure 1 shown.
[0170] The anti-rust and heat-insulating coating of the present invention is modified by mixing potassium silicate with silica sol, and then alkali etching modification treatment is performed with hollow glass microspheres, which can enhance the adhesion and anti-corrosion and anti-rust performance of the coating, making the coating more durable and heat-resistant. In addition, the coating also has a good heat-insulating effect against solar radiation, reduces the energy consumption of air conditioners, and improves the working environment of workers. During construction, the modified silicate has a faster surface drying time than water-based industrial paint due to its strong permeability, water resistance and non-water retention, which greatly improves the second-pass construction efficiency of construction workers.
[0171] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A rust-proof and heat-insulating coating, characterized in that: The raw materials for preparing the anti-rust and heat-insulating coating include the following components in parts by weight: 0.3-0.6 parts of cellulose ether; Dispersant 0.3~0.7 parts; Wetting agent 0.3~0.5 parts; Defoaming agent 0.3~0.5 parts; Stabilizer 0.5~1 part; 0.2~0.5 parts of anti-settling agent; 10~30 parts of heavy calcium; 10-20 parts of titanium dioxide; 3~10 parts of mica powder; Anti-flash rust agent 0.5~1 part; 5-10 parts of acrylic emulsion; 25-45 parts of modified silicate and hollow glass microsphere materials; Thickener 0.3~1 part; 18~25 parts of water; The modified silicate and hollow glass microsphere material is synthesized by two steps of modification of silicate and modification of hollow glass microspheres; The modified preparation method of the silicate comprises the following steps: Mixing silicate, silica sol, organosilicon coupling agent and stabilizer, heating and stirring to obtain modified silicate solution; the heating treatment temperature in the modified preparation method of silicate is 50-75°C; The modification preparation method of the hollow glass microspheres comprises the following steps: The hollow glass microspheres are pretreated and heat treated, and then the modified silicate solution is added to react to obtain the modified silicate and hollow glass microsphere material.
2. The anti-rust and heat-insulating coating according to claim 1, characterized in that: The organic silicon coupling agent is γ-glycidyloxypropyltrimethoxysilane.
3. The anti-rust and heat-insulating coating according to claim 1, characterized in that: The stirring time is 30 to 60 minutes.
4. The anti-rust and heat-insulating coating according to claim 1, characterized in that: The mass ratio of the hollow glass microspheres to the modified silicate solution is 1:(2-3).
5. A method for preparing the anti-rust and heat-insulating coating according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1, weighing the modified silicate, hollow glass microsphere material and acrylic emulsion for pre-reaction; S2, mixing cellulose ether, anti-settling agent, dispersant, wetting agent, defoaming agent, stabilizer, heavy calcium, titanium dioxide, mica powder and anti-flash rust agent; S3, mixing the products obtained in step S1 and step S2, adding a thickener, stirring and reacting to obtain the anti-rust and heat-insulating coating.
6. The preparation method according to claim 5, characterized in that: In step S1, the pre-reaction step is to place the modified silicate, hollow glass microsphere material and acrylic emulsion in a temperature-controlled reactor for stirring reaction.
7. The preparation method according to claim 6, characterized in that: In step S1, the temperature in the temperature-controlled reactor is 40-50°C.
8. The preparation method according to claim 6, characterized in that: In step S1, the stirring speed is 500-550 r / min.
9. The preparation method according to claim 6, characterized in that: In step S1, the stirring time is 30 to 40 minutes.
10. The preparation method according to claim 5, characterized in that: In step S2, the stirring speed is 500-1000 r / min.
11. The preparation method according to claim 5, characterized in that: In step S2, the stirring time is 5 to 25 minutes.
12. The preparation method according to claim 5, characterized in that: In step S3, the stirring speed is 300-400 r / min.
13. The preparation method according to claim 5, characterized in that: In step S3, the stirring time is 8 to 12 minutes.
14. Use of the anti-rust and heat-insulating coating according to any one of claims 1 to 4 in the field of metal material protection.
Citation Information
Patent Citations
Dual-component waterborne thermal-insulation primer and preparation method thereof
CN110041808A
Water-based anticorrosive industrial paint and preparation method thereof
CN115595031A
Base paint emulsion for high-water-resistance and high-weather-resistance multicolor paint and preparation method of base paint emulsion
CN116218313A